Kappa free light chains index in multiple sclerosis very long-term prognosis - Arroyo-Pereiro, Pablo; García-Serrano, Lydia; Morandeira, Francisco; Urban, Blanca; Mas, Virginia; Framil, Mario; León, Isabel; Muñoz-Vendrell, Albert; Matas, Elisabet; Romero-Pinel, Lucía; Martínez-Yélamos, Antonio; Martínez-Yélamos, Sergio; et al. (Frontiers in Immunology, 2023)
The role of the kappa-free light chain (kFLC) in the diagnosis of multiple sclerosis (MS) and, to a lesser extent, its role as a medium-term prognostic marker have been extensively studied. This study aimed to explore its potential as a long-term prognostic marker for MS.We performed an exploratory retrospective observational study by selecting patients systemically followed up in our MS unit with available cerebrospinal fluid and serum samples at the time of initial evaluation. Two groups were defined: benign MS (bMS), defined as patients with Expanded Disability Status Scale (EDSS) ≤ 3 at 10 years of follow-up, and aggressive MS (aMS), defined as patients with EDSS ≥ 6 at 15 years of follow-up. Clinical variables were collected, and the immunoglobulin G (IgG) index, kFLC index, and oligoclonal bands (OCB) were determined for all patients and compared between the groups.Results: Twenty bMS and 15 aMS patients were included in this study. Sixty percent (21/35) were female, and the mean age at the time of the first symptom was 31.5 ± 9.45 years, with no statistical differences between groups. Median follow-up time was 19.8 years (Interquartile range, IQR 15.9-24.6). The median EDSS scores at the last follow-up were 1.5 and 7.5 in the bMS and the aMS group, respectively. No statistically significant differences were found in the kFLC index between the two groups (136.6 vs. 140.27, p=0.59). The IgG index was positive in 62.9% of patients (55% bMS vs. 73.3% aMS, p>0.05), and OCB was positive in 88.6% (90% bMS vs. 86.7% aMS, p>0.05). A significant positive correlation was found between IgG and kFLC indices (rs = 0.85, p<0.001).Given the absence of differences between the two groups with opposite disease courses, it is unlikely that the kFLC index is a reliable and powerful marker of long-term prognosis in MS.